Sistem Monitoring Digital Penggunaan dan Kualitas Kekeruhan Air PDAM Berbasis Mikrokontroler ATMega328 Menggunakan Sensor Aliran Air dan Sensor Fotodiode - Muhammad Kautsar; R. Rizal Isnanto; Eko Didik Widianto (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2015)
Water became one of the staples in the community who are taking a very important role in life. Dependence of human life should not need to denied of water presence. Many activities of human dependent of water such as drinking, washing, bathing etc. In the city, PDAM as a service business into regional water supply solution to deliver water in the houses. Currently, the use of an analog water meter is ineffective for the custumer to be able to monitor the use of water consumption and bill to be paid. Not only that, sometimes the quality of water delivered by the service is not good, it can be seen during the rainy season, which causes the water to become turbid. Today’s technology much shift something analog to digital which is better appearence and easier operation. Thus in this study designed a digital monitoring system using based on microcontroller ATMega 328 by measuring the water discharge from the tube’s connection. For measuring the water usage using the water flow sensor that uses the principle of the hall effect. At the same tool can detect water turbidity problems using photodiode sensor which have working principle by intensity of light received from sample reservoir. The output of this system contains information on water discharge, volume of water in cubic meter also is added to the unit of price. Result of testing the accuracy sensor water flow reached 98,8 % while sensor photodiode had scale measurement water turbidity reacehed 0 - 173 NTU.